Analisis Yuridis Sistem Transaksi Asuransi E-Commerce Dalam Memberikan Perlindungan Hukum Terhadap Para Pemegang Polis - Helvis; Markoni; Julywaty Tenteram (Jurnal Syntax Transformation, 2022)
Insurance from a legal and economic point of view is the main form of risk management used to avoid the possibility of an uncertain loss. Insurance promises protection to the insured against the risks faced by individuals and the risks faced by the company. This study aims to be able to provide data as accurate as possible regarding the object of research so that it is able to explore things that are ideal, then analyzed based on legal theory or applicable laws and regulations. This research method uses qualitative methods using data collection techniques and field research can provide data as accurately as possible about the object of research so that it is able to explore things that are ideal, then analyzed based on legal theory or applicable laws and regulations. Electronic Policy Power as Evidence. Evidence plays an important role in a judicial process. Proof is a way to convince the judge of the truth of the arguments or arguments put forward in a dispute. The juridical protection (E-Policy) for policyholders who conduct insurance transactions by E-Commerce is under the supervision and control of the Financial Services Authority or OJK in accordance with the Regulation of the Financial Services Authority of the Republic of Indonesia Number 21 of 2011 concerning the Financial Services Authority. duties, and authority to regulate and supervise activities in the financial services sector in an integrated, independent, and accountable manner.